Case Report: Ventriculoperitoneal Shunting and Radiation Therapy Treatment in a Cat With a Suspected Choroid Plexus Tumor and Hypertensive Hydrocephalus - Mahon, Elizabeth; Eiras-Diaz, Aldara; Mason, Sarah; Stabile, Fabio; Uriarte, Ane (Frontiers in Veterinary Science, 2022)
A 14-year-old male neutered domestic short-hair cat was presented for a history of behavioral changes and episodes of urinary retention. Neurological examination was consistent with a multifocal intracranial neuroanatomical localization, with suspected right sided lateralisation and suspected raised intracranial pressure (ICP). Brain magnetic resonance imaging (MRI) revealed an intraventricular multilobulated well-defined T2W-hyperintense and T1W-isointense, markedly contrast enhancing mass lesion within the dorsal aspect of the III ventricle extending into the left lateral ventricle, causing hypertensive obstructive hydrocephalus. A ventriculoperitoneal shunt (VPS) was placed within the left lateral ventricle, followed by a radiation therapy (RT) course of 45 Gy total dose in 18 daily fractions. Six-months post-RT, computed tomography revealed mild reduction in mass size and resolution of the hydrocephalus. The patient was neurologically normal with no medical treatment. Raised ICP causes severe clinical signs, can lead to brain ischaemia and herniation, and significantly increases anesthetic risk during RT. Placement of a VPS in cats with hypertensive obstructive hydrocephalus may allow improvement of neurological signs due to raised ICP, and therefore making the patient a more stable candidate for anesthesia and radiation therapy.